2013
DOI: 10.1016/j.immuni.2013.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Interleukin-1 Receptor 2 Binding Prevents Cleavage and Activity of Interleukin-1α, Controlling Necrosis-Induced Sterile Inflammation

Abstract: SummaryNecrosis can induce profound inflammation or be clinically silent. However, the mechanisms underlying such tissue specificity are unknown. Interleukin-1α (IL-1α) is a key danger signal released upon necrosis that exerts effects on both innate and adaptive immunity and is considered to be constitutively active. In contrast, we have shown that necrosis-induced IL-1α activity is tightly controlled in a cell type-specific manner. Most cell types examined expressed a cytosolic IL-1 receptor 2 (IL-1R2) whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
203
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 189 publications
(212 citation statements)
references
References 54 publications
5
203
0
4
Order By: Relevance
“…Also, our observed defects in IL-1α production in calpain KO mice may lead to defects in neutrophil recruitment given recent studies of IL-1α function in promoting neutrophil recruitment to the peritoneum during sterile inflammation [25]. Although both p33 and p17 forms were detected in PLF, a more recent study demonstrates that the calpain-cleaved form of IL-1α (p17) is much more active than p33 in eliciting neutrophils [41]. between WT and KO mice by FACS staining of Gr-1 hi /CD11b hi cells in the peritoneum.…”
Section: Calpain Ko Mice Show Defects In Neutrophil Recruitment and Rmentioning
confidence: 56%
See 2 more Smart Citations
“…Also, our observed defects in IL-1α production in calpain KO mice may lead to defects in neutrophil recruitment given recent studies of IL-1α function in promoting neutrophil recruitment to the peritoneum during sterile inflammation [25]. Although both p33 and p17 forms were detected in PLF, a more recent study demonstrates that the calpain-cleaved form of IL-1α (p17) is much more active than p33 in eliciting neutrophils [41]. between WT and KO mice by FACS staining of Gr-1 hi /CD11b hi cells in the peritoneum.…”
Section: Calpain Ko Mice Show Defects In Neutrophil Recruitment and Rmentioning
confidence: 56%
“…Although release of both p33 and p17 were detected during sterile inflammation, the exact contributions of these cytokines to IL-1R1 signaling was not reported [25]. However, Clarke et al recently demonstrated that cleavage of p33 to p17 by calpains enhances IL-1R1 binding and elicits neutrophils more efficiently than p33 [41]. They also report a soluble receptor (IL-1R2) that prevents cleavage of p33 until inflammasome activation leads to Caspase-1-mediated proteolysis of IL-1R2, thus allowing subsequent cleavage of p33 by calpains [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported previously that several inflammasome activators induce the maturation and secretion of IL-1␣ in a manner dependent on inflammasome components, including ASC (apoptosis-associated speck-like protein containing a CARD [caspase activation and recruitment domain]) and caspase-1 (30)(31)(32)(33). We previously reported that in S. pneumoniae-infected macrophages, the AIM2 and NLRP3 inflammasomes play a critical role in caspase-1 activation and the subsequent processing and secretion of IL-18 and IL-1␤ (11).…”
Section: Resultsmentioning
confidence: 99%
“…Gross Role of Pneumolysin in IL-1␣ Secretion Infection and Immunity contributed to the processing and secretion of IL-1␣ independently of its proteolytic activity, but IL-1␣ secretion was not universally inflammasome dependent, as several particulate NLRP3 activators induced it in the absence of NLRP3, caspase-1, or ASC (30). Zheng et al proposed that IL-1 receptor 2 (IL-1R2) interacts with pro-IL-1␣, which prevents IL-1␣ maturation by calpain, and that caspase-1 cleaves IL-1R2 to resolve this inhibition (33). However, Dewamitta et al reported that the maturation of IL-1␣ in macrophages infected by Listeria monocytogenes is independent of caspase-1 and ASC (26).…”
Section: Discussionmentioning
confidence: 99%